2021
DOI: 10.1038/s41598-020-80013-w
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antibacterial activity of surfactant free Ag–GO nanocomposites

Abstract: Graphene oxide–silver (Ag–GO) nanocomposite has emerged as a vital antibacterial agent very recently. In this work, we report a facile one step route of Ag–GO nanocomposite formation excluding the aid of surfactants and reductants and was successfully applied to negative Escherichia Coli (E coli) to investigate antibacterial activity by varying doze concentration. The successful formation of Ag–GO nanocomposite via facile one step route was confirmed using Fourier transform infrared spectroscopy (FTIR) and Ram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…In the present study, Ag NPs and Ag/RGO NCs exhibited a strong plasma absorption band at ~395 nm ( Figure 2 ). Our results were in agreement with those of other studies [ 42 , 43 ].…”
Section: Resultssupporting
confidence: 94%
“…In the present study, Ag NPs and Ag/RGO NCs exhibited a strong plasma absorption band at ~395 nm ( Figure 2 ). Our results were in agreement with those of other studies [ 42 , 43 ].…”
Section: Resultssupporting
confidence: 94%
“…The results showed that the silver particles are strongly attached to the GO surface and that the Ag/GO composites could inhibit the growth of S. aureus . A one-step route to Ag/GO nanocomposite formation, excluding the need for surfactants and reductants, was reported and a high antibacterial activity of the as-prepared Ag/GO nanocomposite toward E coli was found [ 47 ]. Synthesis, characterization, and antibacterial activity of Ag NPs decorated GO nanocomposite, fabricated by coprecipitation with green reducing agent, were reported also [ 48 ].…”
Section: Antimicrobial Activity and Applications Of Graphene Nanomaterialsmentioning
confidence: 99%
“…Generally, Ag with a smaller size and spherical shape has a higher surface energy than triangular Ag. Higher surface energies are unstable, so Ag NPs easily agglomerate [ 40 ] and diffuse into bacteria at a slow rate [ 41 ], thus reducing their antibacterial effect when compared with Ag NPrsms. The above explanations are possible mechanisms for Ag NPrsms’ superior bactericidal performance.…”
Section: Resultsmentioning
confidence: 99%